2015
DOI: 10.18203/2319-2003.ijbcp20151340
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of Withania somnifera against oxidative damage caused by ethanol in the testes of adult male rats

Abstract: Background: To investigate the effect of Withania somnifera (WS) in preventing the damage caused by alcohol on testis. Methods: Adult male Wistar rats were divided into 4 groups. Group A-control, Group B-WS 200 mg orally, Group C-alcohol 4 g/kg orally, and Group D-WS + alcohol. The sperm parameters were examined. Testicular tissues were examined for biochemical (glutathione [GSH] peroxidase, superoxide dismutase, catalase (CAT), malondialdehyde [MDA]) analysis, and histopathological changes. Results: Biochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…On the other hand, on the reproductive organs, the treatment extract restored ethanol‐induced atrophy on the testicles, epididymis, seminal vesicle and prostate. Similar observations reported in literature (Akomolafe et al., 2015, 2017; Bhargavan et al., 2015; Jang et al., 2011). This loss of sex organ weight observed in the rats ethanol group may be due to reduced bioavailability of sex hormones such as testosterone, luteinising hormone, follicle‐stimulating hormone and inhibin B, whose levels in the blood indicate the male's reproductive endocrine status (Schrader & Marlow, 2014).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…On the other hand, on the reproductive organs, the treatment extract restored ethanol‐induced atrophy on the testicles, epididymis, seminal vesicle and prostate. Similar observations reported in literature (Akomolafe et al., 2015, 2017; Bhargavan et al., 2015; Jang et al., 2011). This loss of sex organ weight observed in the rats ethanol group may be due to reduced bioavailability of sex hormones such as testosterone, luteinising hormone, follicle‐stimulating hormone and inhibin B, whose levels in the blood indicate the male's reproductive endocrine status (Schrader & Marlow, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…This study aimed the evaluation of the effect of the hydro‐ethanolic extract of Rourea coccinea leaves on the toxic effects induced by ethanol on the parameters of testicular activity of Wistar rats. The results obtained established compared to some data in the literature that treatment ethanol of Wistar rats induced toxic effects on reproductive organs, sperm profile and testosteronemia (Adaramoye & Arisekola, 2013; Akomolafe, Akindahunsi, & Afolayan, 2017; Asuquo, Edagha, Ekaundem, & Peter., 2020; Bhargavan et al., 2015; Biney et al., 2020; Jang et al., 2011; Oremosu & Akang, 2014). On these parameters, the hydro‐ethanolic extract of the leaves of Rourea coccinea tested restored these different alterations of testicular activity.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the present study, it was shown that extracts of WS fruits, leaves, stems, and especially roots enhance sperm quality indices such as motility and count in men [ 12 , 20 , 24 , 25 ] and also decrease the effects of chemical toxins on gonads in both men and women [ 13 , 15 , 29 , 33 – 38 , 41 , 44 , 45 , 59 ]. WS can increase gonadal weight in both sexes, enhance folliculogenesis and spermatogenesis, and improve LH, FSH, and testosterone balances [ 15 , 27 , 31 , 35 , 36 , 38 , 42 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 87%
“…In animal studies, WS is known to have gonadotropic function which increases gonadal weight by growthing follicles size in female and also increasing seminiferous tubular cell layers in male animals [ 27 , 28 , 31 , 33 , 35 , 37 , 41 , 57 59 ]. WS is found to improve spermatogenic activity which is proposed to be due to supporting hypothalamic-hypophysial-gonadal hormonal axis and testosterone balance in testes [ 15 , 31 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, effect of the methanolic roots extracts of M. procumbens and O. paniculosa in butanol-induced testicular dysfunction in male rats is reported. Alcohol intoxication is linked to decreased serum levels of testosterone, loss of spermatogenic activity, and testicular atrophy [ 20 , 21 ]. Testosterone synthesis is key to the development of male secondary sexual characteristics and enhancement of sexual desire and also in sperms production [ 22 ].…”
Section: Discussionmentioning
confidence: 99%